2015
DOI: 10.1039/c5an01358e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically monitoring the antibiotic susceptibility of Pseudomonas aeruginosa biofilms

Abstract: The condition of cells in Pseudomonas aeruginosa biofilms was monitored via the electrochemical detection of the electro-active virulence factor pyocyanin in a fabricated microfluidic growth chamber coupled with a disposable three electrode cell. Cells were exposed to 4, 16, and 100 mg L(-1) colistin sulfate after overnight growth. At the end of testing, the measured maximum peak current (and therefore pyocyanin concentration) was reduced by approximately 68% and 82% in P. aeruginosa exposed to 16 and 100 mg L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 47 publications
(65 reference statements)
3
35
0
Order By: Relevance
“…In the following years, several pyocyanin detection approaches were published using disposable screen-printed electrochemical electrodes [ 25 , 30 , 31 , 32 ]. The sensors were single-used and it was argued that the disposability of the electrodes makes them ideal for irreversible electrochemical measurements such as targeting the phenolic oxidation potential of pyocyanin.…”
Section: The Start Of Electrochemical Pyocyanin Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following years, several pyocyanin detection approaches were published using disposable screen-printed electrochemical electrodes [ 25 , 30 , 31 , 32 ]. The sensors were single-used and it was argued that the disposability of the electrodes makes them ideal for irreversible electrochemical measurements such as targeting the phenolic oxidation potential of pyocyanin.…”
Section: The Start Of Electrochemical Pyocyanin Detectionmentioning
confidence: 99%
“…Several sensor designs have been described in the literature, ranging from clean-room fabricated nanograss sensors, conventional rod-electrode setups to cheaper models screen-printed on paper [ 23 , 31 , 32 ]. The fabrication techniques included shadow-printing, ink-jet printing, atomic layer deposition, electrodeposition and electron-beam deposition, while the electrodes where modified with nanoparticles, carbon-nanotubes and nanoalloys in addition to biological modifications to optimize the sensitivity and detection limit [ 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: The Start Of Electrochemical Pyocyanin Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…PYO is also a biological signaling molecule that appears to be engaged in redox‐based signaling . Thus, redox‐probing that can access information of the presence of PYO and its redox‐state should provide important insights of biological activities (e.g., of Pseudomonas infections) …”
Section: Receive Molecular Information Via Redox Modalitymentioning
confidence: 99%
“…Their results showed that tetracycline can facilitate the formation of long filamentous bacteria. In addition to optical imaging and fluorescence, electrochemical sensing [ 53 ] and electrochemical impedance spectroscopy (EIS) [ 54 ] have been used to monitor the activity of biofilm under antibiotic treatment to investigate biofilm antibiotic susceptibility. Recently, Chang et al [ 55 ] demonstrated the formation of biofilm in microfluidic droplets, where biofilm was formed at the interface of double and triple emulsion droplets.…”
Section: Microfluidics For Antibiotic Susceptibility Testingmentioning
confidence: 99%